Broadscale resolving power performance of a high precision uniform field ion mobility-mass spectrometer. Issue 20 (20th July 2015) - May, Jody C.; Dodds, James N.; Kurulugama, Ruwan T.; Stafford, George C.; Fjeldsted, John C.; McLean, John A.
Abstract : 3D surface mapping of the IM-MS instrument performance allows the maximum resolving power to be accessed for any ion system. Abstract : An extensive study of two current ion mobility resolving power theories ("conditional" and "semi-empirical") was undertaken using a recently developed drift tube ion mobility-mass spectrometer. The current study investigates the quantitative agreement between experiment and theory at reduced pressure (4 Torr) for a wide range of initial ion gate widths (100 to 500 μs), and ion mobility values ( K 0 from 0.50 to 3.0 cm 2 V −1 s −1 ) representing measurements obtained in helium, nitrogen, and carbon dioxide drift gas. Results suggest that the conditional resolving power theory deviates from experimental results for low mobility ions ( e.g., high mass analytes) and for initial ion gate widths beyond 200 μs. A semi-empirical resolving power theory provided close-correlation of predicted resolving powers to experimental results across the full range of mobilities and gate widths investigated. Interpreting the results from the semi-empirical theory, the performance of the current instrumentation was found to be highly linear for a wide range of analytes, with optimal resolving powers being accessible for a narrow range of drift fields between 14 and 17 V cm −1 . While developed using singly-charged ion mobility data, preliminary results suggest that the semi-empirical theory has broader applicability to higher-charge state systems.